Ethylene Selectivity in CO Electroreduction when using Cu Oxides: An In Situ ATR‐SEIRAS Study1. Issue 3 (19th December 2017) - Lee, Seunghwa; Lee, Jaeyoung
Abstract: Among all of the known catalysts for CO2 electroreduction, copper oxide materials have the most extraordinary activity and selectivity to multi‐carbon compounds such as ethylene. However, the exact nature of the active surface is not fully understood and, thus, there have been different points of view on the origin of the remarkable catalytic properties. By using in situ attenuated total reflectance surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS), we show that carbon monoxide (CO) binds more strongly on the surface of copper oxides than on pure metallic copper and, consequently, the prolonged population of CO, a key intermediate of CO2 reduction, is observed. The high CO coverage could be a key factor that can explain the propensity of CO2 and CO electroreduction to ethylene in general but there have been a number of controversial factors in the research field of CO2 reduction. To the best of our knowledge, this is the first report that presents direct evidence for the hypothesis relating stronger CO binding and higher CO coverage to enhanced ethylene selectivity on the copper oxide catalyst relative to metallic copper based on in situ real‐time observations. This ATR‐SEIRAS application provides general phenomenological insights into the ethylene selectivity in CO electroreduction when using a copper‐based system. Abstract : Tightly bound : By using in situ attenuated total reflectance surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS), it is shown that carbon monoxide (CO) binds more strongly on the surface of copper oxides than on pure metallic copper and, consequently, the prolonged population of CO, a key intermediate of CO2 reduction, is observed.